EVALUASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI KELAUTAN DAN PERIKANAN RI NO.PER.06/MEN/2011 DI KABUPATEN GRESIK - Nodi Marefanda (Universitas Teuku Umar, 2017)
This Research is about evaluation of the National Program for Community Empowerment of Marine and Fishery, in the matter of society business of salt empowerment in Prambangan Village, Kebomas District, Gresik Country. The purpose of study is to answer the problem of the study. And the research focus on: compile of detail planning for society business of salt empowerment at the Village Level, Distribution of community grants, increase of institutional capacity and Human Resources of Salt Farmers and Facilitation of partnership in society business of salt. This research use qualitative and descriptive methods. In collecting the data, researchers use the approach of observation, interviews, and focus discussion group. The techniques to analyze data is undertook qualitatively through steps of data reduction, data presentation and conclusion. Analysis was done by focusing on the findings of the data that has been gathered and the relevant information from the list of literature (secondary data). This research uses the evaluation and policy theory by FrankThomas J.Cook P.Schioli, Jr. and institutional theory. The results of this study find that the implementation of the National Program for independent society of empowerment of marine and fishery on society business of salt empowerment, which include: arrangement of detail planning of society business of salt empowerment in the Village Level, Distribution of community grants (CG), increase of institutional capacity and Human Resources (HR) of Salt Farmers provide yet an impacts expected and Facilitation of partnership in society business of salt do not provide yet an impact expected.Keywords: Evaluation, NPCEMF, CG SBSE